Liveability and low-income housing in Nigeria - Mohit, Mohammad Abdul; Iyanda, Sule Abbas (Elsevier, 2016)
This study examined the quality of life against the backdrop of the existing environment in the public low-income housing estates. Based on the desktop literature the study used both subjective and objective measurements to investigate the liveability of the selected housing estates. Home environment, neighbourhood amenities, economic vitality, social environment and civic protection were examined. The stratified random sampling was used in distributing questionnaire to household heads in all types of homes. Data were analysed with descriptive statistics and structural equation modelling (SEM). This study contributes to the existing body of knowledge in liveability studies in terms of model construct.